Stakeholder Identification in Internal Control of Building Construction using Design and Build Contract to Improve Efficiency and Effectiveness - Marastuti, Putri; Riantini, Leni Sagita (International Journal of Science, Technology & Management, 2024)
The amount of infrastructure development in Jakarta makes internal control of the implementation of design and build contracts for the construction of state buildings need attention. The problem in internal control is there are still some recurring findings and supervisory findings that are not detected by Government Internal Supervisory Apparatus (APIP) but found by external auditors, as well as delays in completing assignments. The problems include a limited number of technical auditors, uneven knowledge, and experience of construction supervision, overlapping assignments, and a report process that takes time. These problems can have an impact on the implementation of internal control, that is lack of achievement of internal control objectives and the potential for non-compliance with the construction process with laws and regulations, thus showing that internal control of construction is not running effectively and efficiently. To improve efficient and effective internal supervision of construction, it is necessary to standardize operational procedures (SOP) or work procedures for internal control of construction, especially for design and build contracts. This research aims to identify stakeholders and the roles and responsibilities of each party in internal control of building construction using design and build contract to improve efficiency and effectiveness. The results reveal a set of internal and external stakeholders as well as the form of organizational structure and the relationship of coordination and responsibility lines. The results of this research also emphasize the roles and responsibilities of each stakeholder so that each party fully understands the obligation to carry out internal supervision assignments for design and build construction.